Human pathogenic Yersinia species - Bliska, James (Henry Stewart Talks, 2009)
Classification of strains, Different degrees of pathogenicity, Intestinal Yersinia infections: transmission and outcomes, Transmission modes of Y. pestis, Pneumonic and bubonic plague, Adhesion and invasion, Invasin, Gene expression, Vacuole trafficking, Secretion systems